Comparative study to evaluate in vivo and in vitro antioxidant potential of processed and unprocessed Curcuma logna L. using Allxon induced diabetic rats - Parashare VM; Nikam S; Nade VS; Pande Shishir (International Journal of Life Sciences, 2017)
The present study was aimed to investigate in vivo, in vitro antioxidant activity of the processed curcuma Longa L. turmeric (PT) and unprocessed curcuma Longa L. (UPT). Both the extract are subjected to qualitative phytochemical screening. In in-vitro antioxidant properties total Phenolic content in each extract was determined using Gallic acid as a standard, calibration curve was prepared. The result is expressed as mg of Gallic acid equivalent per gram of extract. For unprocessed turmeric (UPT) and processed turmeric (PT) the values were 2.4 mg of GAE/g and 2.1mg of GAE/g. respectively. In in-vitro antioxidant properties total flavonoid content was determined in each extract using Quercetin as reference standards. Total flavonoid content in methanolic extract of UPT and PT in terms of quercetin equivalent (QE) was 152.25mg/100 g and 37.98mg/ 100 g of dry extract respectively. Total antioxidant activity of UPT and PT extract in terms of ascorbic acid equivalent (AAE) was 6.394 and 3.922 mg/ ml of extract respectively. In- vivo study involved five groups of each comprising six Wistar rats (250 - 300 kg) and labelled as Hyperglycemic, Normal, Standard drug Glipizide, UPT treated and PT treated. Besides the Normal group Alloxan was administered in all animals as a single dose (50 mg/kg, i.v.) to induce diabetes. A dose of 300 mg of processed and unprocessed turmeric/kg of body weight was evaluated using acute toxicity test. It is orally administered daily for four weeks after induction of diabetic. The fasting blood glucose level was measured. The animal whose glucose level did not rise to more than 250mg/dl was rejected. Only animals that presented with glycemic levels equal to or above 250 mg/dl were submitted to treatments, which consisted of a daily administration of the UPT and PT turmeric for 21days. It was considered as a first day and blood samples (Approximately 0.5ml) were collected from rats by puncturing the retro orbital sinus, under mild ether anesthesia on 1st,7th, 14th 21st day for glucose estimations using GOD-POD method. At the same time urine sugar was estimated using Diastic. At the end of the study all groups rats pancreases were removed, labelled, were minced and 10% (W/V) tissue homogenate was prepared using 0.1 M Phosphate buffer (PH 7.4) in a Potter- Elvehjem type homogenizer and used to enzyme assay. The comparison using statistical analysis ANOVA was performed. Decrease level of lipid peroxidase as compare to Diabetic, increase in superoxide dismutase (SOD) and catalase (CAT) activity are statistically analysed.( p<0.05).These findings suggest that the UPT has potent antioxidant and antidiabetic activity, which may be responsible for some of its reported pharmacological activities and can be used as antioxidant supplement. Substances, chemicals rendering anti-oxidative properties can attenuate alloxan toxicity.